2021
DOI: 10.3390/cimb43020052
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Resveratrol on Human Retinal Pigment Cells and a Myopia Animal Model

Abstract: Resveratrol is a key component of red wine and other grape products. Recent studies have characterized resveratrol as a polyphenol, and shown its beneficial effects on cancer, metabolism, and infection. This study aimed to obtain insights into the biological effects of resveratrol on myopia. To this end, we examined its anti-inflammatory influence on human retinal pigment epithelium cells and in a monocular form deprivation (MFD)-induced animal model of myopia. In MFD-induced myopia, resveratrol increased coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
(52 reference statements)
1
20
0
2
Order By: Relevance
“…Collagen disorders are exacerbated by the activation of the nuclear factor-κB, which increases the expression of matrix metalloproteinase 2 while reducing the activity of the tissue MMP2 inhibitor [ 120 ]. Hsu et al found shorter eyes in hamsters treated with RSV than in the group that had not been treated with RSV [ 121 ]. A decrease in resveratrol-treated eyes has been observed in myopia-related tissue remodeling proteins and the expression of inflammatory cytokines (NFκB, TGF-β, MMP2, TNFα, IL-6, and IL-1β).…”
Section: Resveratrol In Eye Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen disorders are exacerbated by the activation of the nuclear factor-κB, which increases the expression of matrix metalloproteinase 2 while reducing the activity of the tissue MMP2 inhibitor [ 120 ]. Hsu et al found shorter eyes in hamsters treated with RSV than in the group that had not been treated with RSV [ 121 ]. A decrease in resveratrol-treated eyes has been observed in myopia-related tissue remodeling proteins and the expression of inflammatory cytokines (NFκB, TGF-β, MMP2, TNFα, IL-6, and IL-1β).…”
Section: Resveratrol In Eye Diseasesmentioning
confidence: 99%
“…In addition, collagen I expression increase in eyes treated with resveratrol was noted. This might suggest that resveratrol exhibits a regulation pattern similar to atropine [ 121 ].…”
Section: Resveratrol In Eye Diseasesmentioning
confidence: 99%
“…Inflammatory cytokines IL-6 and TNF-α in the retina may serve as triggers to initiate MMP-2 activity in the retina, followed by sclera (Yuan et al 2019 ), causing progressive scleral remodeling and myopia. Moreover, resveratrol, a naturally occurring antioxidant, has been shown to ameliorate myopia development by blocking the relevant signaling pathways of inflammatory effects above (Hsu et al 2021 ; Jiang et al 2019 ; Wei et al 2019 ).…”
Section: Potential Biological Mechanisms Of Air Pollutants On Myopiamentioning
confidence: 99%
“…Proanthocyanidins and resveratrol enhance the expression of vascular endothelial growth factor (VEGF) in pigment cell culture [ 124 , 125 ] and animal model (hamsters) [ 126 ].…”
Section: The Beneficial Effects Of Polyphenols On Health and Its Mole...mentioning
confidence: 99%